2019
DOI: 10.1186/s12893-019-0532-6
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis following bariatric surgery

Abstract: Background The laparoscopic Roux-en-Y gastric bypass (LRYGBP) is the second most performed bariatric surgical procedure. With the increasing number of patients undergoing bariatric surgery, the number of complications is also growing. Early diagnosis and treatment of the complications is crucial. Case presentation A very unusual complication was met after an uneventful laparoscopic gastric bypass (LGBP) procedure due to an obstructing blood clot in the biliairy limb res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A cohort study reported 3.5 years as the average median time from bariatric surgery to developing acute pancreatitis, with the most common etiology being gallstones [ 12 ]. The formation of gallstones is likely facilitated by rapid weight loss after surgery [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cohort study reported 3.5 years as the average median time from bariatric surgery to developing acute pancreatitis, with the most common etiology being gallstones [ 12 ]. The formation of gallstones is likely facilitated by rapid weight loss after surgery [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study reported 3.5 years as the average median time from bariatric surgery to developing acute pancreatitis, with the most common etiology being gallstones [ 12 ]. The formation of gallstones is likely facilitated by rapid weight loss after surgery [ 12 ]. Additionally, postoperative anastomotic strictures, leak, ductal dilation, sludge, and choledocholithiasis have been linked with the development of postoperative acute pancreatitis [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pancreatitis directly following bariatric surgery is a very uncommon complication. A literature review revealed very few cases of acute pancreatitis postbariatric surgery [3][4][5][6]. Here, we present a rare case of acute pancreatitis following LSG in the early post-operative period to increase the awareness of bariatric surgeons of the complications of this surgery.…”
mentioning
confidence: 89%